Temporality as the co-construction of couple relationship: The regulation of experiential time. (December 2018) - Molina, María Elisa; Tapia-Villanueva, Luis; Fossa, Pablo
A study of temporality in human encounters and specifically in amorous relationships is presented. The article aims to analyze subjective and experiential time, focusing on the relationships and the difficulties involved. A review of the theoretical and phenomenological understanding of temporality that gives rise to the Chronogenesis model is made. The authors describe time processing in a couple's experience through an analysis of fictional literature and clinical vignettes. Moments of dialogue are addressed to focus on the relationship as an emergent process, the co-construction of the relationship, "weness, " and a sense of future possibilities in which the partners reposition and negotiate.